Cooling therapy in severe neonatal asphyxia: a case of hypoxic-ischemic encephalopathy with neonatal pneumonia and neurological recovery - Aliya Sari; Syibra Sabrina; Neni Sumarni (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2026)
Background: Neonatal asphyxia, defined as failure to establish breathing at birth, remains a major contributor to early neonatal mortality, causing around 900.000 deaths globally each year. One of its most serious complications is hypoxic-ischemic encephalopathy (HIE), a brain injury due to oxygen deprivation leading to a long term neurological impairment. Up to 60% of infants with severe HIE die or develop profound disability. Early cooling therapy reduces mortality and improves neurodevelopmental outcomes. Comorbidities such as pneumonia may complicate management. This case describes a neonate with severe asphyxia and HIE with pneumonia, and its purpose is to elucidate a case of severe neonatal asphyxia with HIE and pneumonia successfully managed with early cooling therapy as evidence of effective neuroprotective. Case Presentation: A male neonate born at 38 weeks by cesarean section due to fetal distress had meconium-stained amniotic fluid. Apgar scores of 1-2-5. The patient underwent resuscitation with intubation, ventilation, and meconium suctioning. Seizures developed at 20 minutes of life. Examination showed chest retraction and coarse crackles. Babygram showed pneumonia, while cranial ultrasonography indicated increased intracranial pressure. Labs revealed hypercalcemia and prolonged coagulation. Supportive therapy included oxygen, IV glucose, antibiotics, calcium gluconate, fluids, and anticonvulsants. Cooling therapy was initiated within 6 hours, maintained for 72 hours at 33.5–34.5°C, followed by gradual rewarming. Neurological reflexes improved, and the patient was successfully extubated. Conclusion: Cooling therapy remains a cornerstone for HIE after severe neonatal asphyxia. Early initiation within six hours, with careful monitoring and infection control, can significantly improve neurological outcomes even in complicated cases.